Are There Race‐Based Differences in Neuropsychological Test Performance and Psychological Symptom Endorsement Among Adults Diagnosed With ADHD? - Matthew S. Phillips; Mira I. Leese; Steven A. Abalos; Greg Shapiro; Kailyn Bare; Nevin A. Orleans; Nicole M. Durkin; Jason R. Soble (Psychiatric Research and Clinical Practice)
Objective Prevalence rates of attention‐deficit/hyperactivity disorder (ADHD) vary by several demographic factors, including sex, socioeconomic status, geographic region, and race/ethnicity, with higher rates seen among non‐Hispanic White children and adults compared to racially/ethnically minoritized individuals. This study investigated if similar race‐based differences exist in neurocognitive test performance and psychiatric/ADHD symptom reporting among groups in a demographically diverse sample. Methods Data from 491 adults with a confirmed diagnosis of ADHD were analyzed to assess for differences in broad neurocognitive domains (i.e., learning and memory, attention/working memory, processing speed, and executive functions), as well as on measures of mood and ADHD‐related symptomatology. Results Findings largely demonstrated comparable neurocognitive test performance and ADHD and psychiatric symptom endorsement across racial groups with a known diagnosis of ADHD. Conclusions Although prior research has consistently documented racial/ethnic disparities in rates of ADHD diagnosis, current results largely did not demonstrate neuropsychological performance‐based differences among demographically diverse patients diagnosed with ADHD. Relevance to clinical practice ADHD is one of the most prevalent neurodevelopmental disorders in the U.S. and constitutes a large number of referrals for diagnostic evaluation. Despite disparities in rates of diagnosis among broad racial/ethnic groups, neuropsychological outcomes remain largely consistent among these groups.